Progress in Carotenoid Research - Queiroz Zepka, Leila; Jacob-Lopes, Eduardo; Vera De Rosso, Veridiana (IntechOpen, 2018)
The book "Progress in Carotenoid Research" presents an authoritative and comprehensive overview of the biology, biochemistry, and chemistry of carotenoids. Divided into 14 discrete parts, this book covers topics on basic science and applied technology of carotenoid molecules. This book provides an insight into future developments in each field and has an extensive bibliography. It will be an essential resource for researchers and academic and industry professionals in the natural pigment field.